Small group discussions for analysis - Cook, Roger, 1944-; Jurma, William E.; Educational Video Group (Greenwood, IN : Educational Video Group, 2005)
Using research appropriate to the topic, two separate groups discuss a particular question. The participants in the second group also analyze group discussions
Question of fact : are SATs an accurate predictor of college success? -- Question of value : should marijuana be legalized for medicinal and/or general use?
Executive producer, Roger Cook ; educational consultant, William Jurma.
DVD
English
No Master.
Keywords: Communication in small groups; Discussion; Group problem solving